Comparing the pre-SNe feedback and environmental pressures for 6000 H ii regions across 19 nearby spiral galaxies. Issue 4 (19th October 2021) - Barnes, A T; Glover, S C O; Kreckel, K; Ostriker, E C; Bigiel, F; Belfiore, F; Bešlić, I; Blanc, G A; Chevance, M; Dale, D A; Egorov, O; Eibensteiner, C; et al.
ABSTRACT: The feedback from young stars (i.e. pre-supernova) is thought to play a crucial role in molecular cloud destruction. In this paper, we assess the feedback mechanisms acting within a sample of 5810 H ii regions identified from the PHANGS-MUSE survey of 19 nearby (<20 Mpc) star-forming, main-sequence spiral galaxies [log( M ⋆ /M⊙ ) = 9.4–11]. These optical spectroscopic maps are essential to constrain the physical properties of the H ii regions, which we use to investigate their internal pressure terms. We estimate the photoionized gas ( P therm ), direct radiation ( P rad ), and mechanical wind pressure ( P wind ), which we compare to the confining pressure of their host environment ( P de ). The H ii regions remain unresolved within our ∼50–100 pc resolution observations, so we place upper ( P max ) and lower ( P min ) limits on each of the pressures by using a minimum (i.e. clumpy structure) and maximum (i.e. smooth structure) size, respectively. We find that the P max measurements are broadly similar, and for P min the P therm is mildly dominant. We find that the majority of H ii regions are overpressured, P tot / P de = ( P therm + P wind + P rad )/ P de > 1, and expanding, yet there is a small sample of compact H ii regions with P tot, max / P de < 1 (∼1 per cent of the sample). These mostly reside in galaxy centres ( R gal < 1 kpc), or, specifically, environments of high gas surface density; log(Σgas /M⊙ pc −2 ) ∼ 2.5 (measured on kpc-scales). Lastly, we compare to a sample of literature measurements for P therm and P rad to investigate how dominant pressure term transitions over around 5 dex in spatial dynamic range and 10 dex in pressure.